2017
DOI: 10.5551/jat.rv17012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Lowering Therapy and Circulating PCSK9 Concentration

Abstract: Hypercholesterolemia, particularly an increase in low-density lipoprotein cholesterol (LDL-C) levels, contributes substantially to the development of coronary artery disease and the risk for cardiovascular events. As the first-line pharmacotherapy, statins have been shown to reduce both LDL-C levels and cardiovascular events. However, despite intensive statin therapy, a sizable proportion of statin-treated patients are unable to achieve the recommended target LDL-C levels, and not all patients can avoid future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 98 publications
(136 reference statements)
4
82
0
1
Order By: Relevance
“…In addition to inflammatory conditions, plasma PCSK9 levels are elevated by the use of lipid‐lowering drugs, such as statins . We observed a similar upregulation of plasma PCSK9 in bacteraemia patients using statins, but also identified other factors that were associated with lower plasma PCSK9 levels (male sex, liver disease and alcohol abuse).…”
Section: Discussionsupporting
confidence: 65%
“…In addition to inflammatory conditions, plasma PCSK9 levels are elevated by the use of lipid‐lowering drugs, such as statins . We observed a similar upregulation of plasma PCSK9 in bacteraemia patients using statins, but also identified other factors that were associated with lower plasma PCSK9 levels (male sex, liver disease and alcohol abuse).…”
Section: Discussionsupporting
confidence: 65%
“…With regard to the proteins involved in lipid metabolism proteins, LDLR is a carrier that removes cholesterol and regulates its amount (Kamisako et al, 2014). PCSK9 binds to LDLR, in which LDL particles cannot be transferred into the cells (Kamisako et al, 2014;Nozue, 2017). The enzyme CYP7α1 is important for the synthesis of bile acid and the regulation of cholesterol levels (Chiu, Chang, Liu, & Chiang, 2017;Mohammadi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Proprotein convertase subtilisin/kexin type 9 (PCSK9) is an enzyme also accepted as a new biomarker for lipid metabolism, a novel pharmacological target for hypercholesterolemia, since the inhibition of PCSK9 may be one of the management options to decrease CVD risk [42, 43]. PCSK9 is primarily synthesized by the liver, intestine, and kidney as a precursor of the 75 kDa protein; it then undergoes autocatalytic cleavage in the endoplasmic reticulum and secreted as a heterodimer protein [43].…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 Effect On Lipimentioning
confidence: 99%
“…PCSK9 is primarily synthesized by the liver, intestine, and kidney as a precursor of the 75 kDa protein; it then undergoes autocatalytic cleavage in the endoplasmic reticulum and secreted as a heterodimer protein [43]. PCSK9 causes a reduction in the number of LDL cholesterol receptor by enhancing the degradation of hepatic LDL receptor and this reduces LDL cholesterol uptake leading to a subsequent increase in circulating LDL cholesterol levels [43, 44]. In addition, recent studies showed that very low-density lipoprotein receptor and apolipoprotein E2 receptor are also partly regulated by PCSK9 [45].…”
Section: Proprotein Convertase Subtilisin/kexin Type 9 Effect On Lipimentioning
confidence: 99%